Integrated strategy for anti-fatigue markers screening of gonads of Rana temporaria chensinensis David based on comprehensive chemical analysis and in vivo activity - Zhongyao Wang; Yunhe Liu; Yue Zhou; Shihan Wang; Xinxin Xu; Xuanrui Fan; Miao Chen; Yong Yang; Zhihan Wang; Yongsheng Wang (Journal of Functional Foods, 2023)
This work is the first attempt to reveal the chemical compositions, as well as the relationships between the chemical compositions and anti-fatigue effect of Oviductus Ranae (OR) and Rana chensinensis ovum (RCO). In this work, an integrated strategy was applied containing comprehensive chemical profiling analysis, extraction methods, in vivo study, multivariate statistics, and network pharmacology. Here, 138 compounds were identified or briefly characterized using UPLC-Q/TOF-MS. About 24 and 35 variables were considered to be discriminating compounds from petroleum ether and ethanol extracts of OR and RCO, respectively. In addition, 41 identified compounds in OR and RCO were significantly correlated with anti-fatigue parameters. Finally, 22 candidate markers in OR and RCO were screened. Network pharmacology analysis was employed to verify those markers and screen the potential targets for anti-fatigue effect. Screened targets were further validated using RT-PCR. In muscle tissues, AKT mRNA, PI3K mRNA, and mTOR mRNA were upregulated following OR and RCO administration. This work not only paved the way for further study of OR and RCO in anti-fatigue function, but also provided essential information for their products quality control.